The innate immune response to lower respiratory tract E. Coli infection and the role of the CCL2-CCR2 axis in neonatal mice. (September 2017) - McGrath-Morrow, Sharon A.; Ndeh, Roland; Collaco, Joseph M.; Poupore, Amy K.; Dikeman, Dustin; Zhong, Qiong; Singer, Benjamin D.; D'Alessio, Franco; Scott, Alan
Highlights: Neonatal lung exhibits delayed recruitment of innate immune cells to E. coli bacteria. Absence of an intact CCL2-CCR2 axis in the neonate increases mortality to E. coli. Postnatal age is a major factor in the lungs innate immune response to E. coli. Abstract: Neonates have greater morbidity/mortality from lower respiratory tract infections (LRTI) compared to older children. Lack of conditioning of the pulmonary immune system due to limited environmental exposures and/or infectious challenges likely contributes to the increase susceptibility in the neonate. In this study, we sought to gain insights into the nature and dynamics of the neonatal pulmonary immune response to LRTI using a murine model. Methods: Wildtype (WT) and Ccr 2 −/− C57BL/6 neonatal and juvenile mice received E. coli or PBS by direct pharyngeal aspiration. Flow cytometry was used to measure immune cell dynamics and identify cytokine-producing cells. Real-time PCR and ELISA were used to measure cytokine/chemokine expression. Results: Innate immune cell recruitment in response to E. coli- induced LRTI was delayed in the neonatal lung compared to juvenile lung. Lung clearance of bacteria was also significantly delayed in the neonate. Ccr 2 −/− neonates, which lack an intact CCL2-CCR2 axis, had higher mortality after E. coli challenged than Ccr 2 +/+ neonates. A greater percentage of CD8 + T cells and monocytes from WT neonates challenged with E. coli produced TNF compared to controls. Conclusion: The pulmonary immune response to E. coli- induced LRTI differed significantly between neonatal and juvenile mice. Neonates were more susceptible to increasing doses of E. coli and exhibited greater mortality than juveniles. In the absence of an intact CCL2-CCR2 axis, susceptibility to LRTI-induced mortality was further increased in neonatal mice. Taken together these findings underscore the importance of age-related differences in the innate immune response to LRTI during early stages of postnatal life.